2023
DOI: 10.3389/feart.2022.1036339
|View full text |Cite
|
Sign up to set email alerts
|

Study on rock mass failure characteristics of double-hole delayed blasting in interbedding based on particle expansion algorithm

Abstract: The existence of the interface between soft and hard rock often makes it difficult to control the blasting effect. Studying the influence of structural plane and delayed initiation time on rock blasting characteristics can make the blasting effect more controllable. In this paper, by using the Particle Flow Code (PFC2D) and particle expansion algorithm, the double-hole delayed blasting experiments of soft-hard rock are carried out, and the results are analyzed from the perspectives of fragment gradation, micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…Four boundaries of the model are subjected to the compression pressure of P (P is 5 MPa), and application method of compression pressure is adopted, which is suggested by Cundall et al 32 .
Figure 4 Discrete element method model of single-hole sandstone blasting 33 .
…”
Section: Establishment Of Blasting Numerical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Four boundaries of the model are subjected to the compression pressure of P (P is 5 MPa), and application method of compression pressure is adopted, which is suggested by Cundall et al 32 .
Figure 4 Discrete element method model of single-hole sandstone blasting 33 .
…”
Section: Establishment Of Blasting Numerical Modelmentioning
confidence: 99%
“…6 , the reasonableness of the blasting method can be proved by contrast with analytical solutions of the stress with the experimental values.
Figure 6 Verification of peak stress of coupled stress field 33 .
…”
Section: Establishment Of Blasting Numerical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…At the practical application level, Yuan et al 9 studied the damage mechanism of the tunnel envelope under the coupling of vertical geostress and blasting load. Cui et al [10][11][12] analyzed the change law of high geostress soft and hard rock formations under blasting load from the levels of crack state, contact coefficient, and energy magnitude. Yang et al 13 studied the influence of geostress on the degree of blast energy decay from the perspective of blast energy decay; and with the help of borehole blasting excavation method, they found that dynamic stress redistribution after explosive blast is the most important factor leading to rock damage 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Regarding other engineering levels, Yuan et al 23 provided a methodological basis for increasing the mining rate of uranium ore by using blasting and fracturing techniques to expand the tiny cracks in the rock body and increase the permeability of uranium-bearing sandstone. Cui et al [24][25][26] took the blasting of weakly interbedded rock as a research point. They analyzed the influence of weakly interbedded rock on the blasting effect regarding crack effect, stress field, energy field, etc.…”
Section: Introductionmentioning
confidence: 99%